THE EFFECT OF COMPANY SIZE, REPUTATION OF AUDITOR, PUBLIC OWNERSHIP, AND COMPANY AGE ON AUDIT DELAY (STUDY ON MANUFACTURING COMPANIES LISTED ON THE IDX IN 2018) - REZA ISNARGONO ISNARGONO (Jurnal Ilmiah Mahasiswa FEB, 2019)
This research aims to examine the influence of Company Size, Reputation of Auditor, Public Ownership, and Age of Company on audit delay on manufacturing company listed on IDX in 2018. The approach in this study is a quantitative approach because this research is presented with numbers and try to see the effect of company size, reputation of auditor, ownership and age of the company on audit delay in the manufacturing companies listed on the Indonesia Stock Exchange in 2018. The sample was gathered using purposive sampling with specific criteria. Based on the sampling technique presented, the number of samples taken in 2018 are 159 Manufacturing Companies. The data analysis technique in this research used descriptive analysis, multiple regression test, the classical assumption test, and hypothesis used t test and determination R2 with the help of SPSS software version 23. The results of this research indicate that Company Size has a negative influence on Audit Delay, Reputation of Auditor has no influence on audit delay, Public Ownership has no influence on the audit delay, and Age of Company has no influence on audit delay. Keywords: Company size, Reputation of Auditor, Public Ownership, Age of Company, Audit Delay